Tone Sandhi : patterns across Chinese dialects - Chen, Matthew Y. (Cambridge, UK ; New York : Cambridge University Press, 2000)
Matthew Chen's landmark study offers the most comprehensive analysis to date of the rich and complex patterns of tone used in Chinese languages. His book, the culmination of a ten-year research project, explores a range of important theoretical issues against a wealth of empirical data not previously accessible to linguists.
Cover; Half-title; Series-title; Dedication; Title; Copyright; Contents; Preface; Notational conventions; 1 Setting the stage; 2 Tonal representation and tonal processes; 3 Directionality and interacting sandhi processes I; 4 Directionality and interacting sandhi processes II; 5 From base tones to sandhi forms: a constraint-based analysis; 6 From tone to accent; 7 Stress-foot as sandhi domain I; 8 Stress-foot as sandhi domain II; 9 Minimal rhythmic unit as obligatory sandhi domain; 10 Phonological phrase as a sandhi domain; 11 From tone to intonation; Concluding remarks.
Includes bibliographical references (pages 507-522).
Print version record.
eBooks on EBSCOhost
Keywords: Chinese language -- Tone; Chinois (Langue) -- Ton; FOREIGN LANGUAGE STUDY -- Chinese; Chinese language -- Tone; Mundart; Sandhi; Chinees; Toon (taalkunde); Dialecten; Sandhi; Chinois (langue) -- Ton; Langues chinoises; Chinois (langue) -- Intonation; Chinois (langue) -- Phonétique.; Sandhi; Chinesisch; Electronic books; Electronic books